KECENDERUNGAN MANAJEMEN LABA PADA INDUSTRI TEKSTIL DAN PRODUK TEKSTIL DI BURSA EFEK INDONESIA YANG DIPREDIKSI MENGALAMI KEBANGKRUTAN - AGNES UTARI WIDYANINGDYAH; OCTA FENNY LISTIYANA (Jurnal Bisnis dan Akuntansi, 2009)
This research objective is to explore earnings management’s indication in listed textile company of Jakarta Stock Exchange which was predicted bankrupt during 2004-2006 periods with Altman Z score. Hypothesis is tested using one sample t test. From the sample tested there was earnings management indication during bankrupt’s prediction period. This result of research shows firm with 3 years in loss tends to do earnings management. In advance, this study is supports signaling theory which explain that if firm’s performance and its prospect is bad, the manager records negative discretionary accruals as signal where current and next profit worse than current non-discretionary accruals to inform the market that manager has strong confident to solve the problems and show the managerial quality. With this signal, manager expects market appreciation to handle stock’s price decreasing.